2015
DOI: 10.1016/j.ocemod.2015.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Decimation and Interpolation (PDI) method for a baroclinic non-hydrostatic model

Abstract: Non-hydrostatic models are computationally expensive in simulating density flows and mass transport problems due to the requirement of sufficient grid resolution to resolve density and flow structures. Numerical tests based on the Non-Hydrostatic Wave Model, NHWAVE [Ma et al., 2012], indicated that up to 70% of the total computational cost may be born by the pressure Poisson solver in cases with high grid resolution in both vertical and horizontal directions. However, recent studies using Poisson solver-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…This observation, and inspired by the work of Van Reeuwijk (2002) and Shi et al (2015), motivates us to solve the vertical and horizontal momentum balances on essentially separate grids. The vertical balance (and pressure) is evaluated on a coarse grid of which the resolution is dictated by the wave motion, whereas the horizontal balance is solved on a finer grid to account for vertical shear.…”
Section: Introductionmentioning
confidence: 90%
“…This observation, and inspired by the work of Van Reeuwijk (2002) and Shi et al (2015), motivates us to solve the vertical and horizontal momentum balances on essentially separate grids. The vertical balance (and pressure) is evaluated on a coarse grid of which the resolution is dictated by the wave motion, whereas the horizontal balance is solved on a finer grid to account for vertical shear.…”
Section: Introductionmentioning
confidence: 90%
“…Ma et al [41] extended the application of NHWAVE by considering the baroclinic pressure forcing in the momentum equation. To decrease the time consumed in solving the Poisson equation, Shi et al [42] added a pressure decimation interpolation (PDI) method into NHWAVE, which can greatly improve the model's efficiency without significantly impacting the model's accuracy obviously.…”
Section: Numerical Modelmentioning
confidence: 99%
“…in which h(x, y) is water depth and η(x, y) is free surface elevation relative to still water level, (1) and (2) can be written in a compact, conservative form in the σ-coordinate (Shi et al, 2015):…”
Section: Governing Equationsmentioning
confidence: 99%
“…These simplifications also considerably reduce the computational requirements of the model. The Pressure Decimation and Interpolation (PDI) Method was added to NHWAVE by Shi et al (2015), who confirmed that the dynamic pressure can be modeled accurately with only a small number of vertical layers. This significantly increased model efficiency for simulating non-hydrostatic, baroclinic processes.…”
Section: Introductionmentioning
confidence: 95%